Identification and Analysis of Barriers to the Realization of Synergy Between the Supreme Audit Court of Iran and Internal Auditing in the National Iranian South Oil Company - Bouzar, Aref; Mahmoudi, Ali; Hosseinzadeh, Ali Hossein; Zolfaghari, Parisa (Business, Marketing, and Finance Open, 2026)
This study aims to identify and analyze the barriers hindering the realization of synergy between the Supreme Audit Court of Iran and internal auditing within the National Iranian South Oil Company. The research employs a qualitative approach based on grounded theory. Data were collected through semi-structured interviews with experts in auditing and financial supervision and analyzed using open, axial, and selective coding methods. The findings indicate that barriers to achieving synergy fall into seven main categories: structural and organizational barriers, legal and regulatory barriers, cultural and behavioral barriers, human resource constraints, technological and information system barriers, political and managerial challenges, and finally, financial resource limitations. The results reveal that the presence of these barriers reduces the effectiveness of collaboration and synergy between the Supreme Audit Court and internal auditing, thereby affecting the efficiency of the supervisory system in large state-owned enterprises. The precise identification of these barriers can provide a foundation for designing corrective strategies and enhancing institutional synergy to promote transparency, accountability, and financial integrity in public sector organizations.